Microbial fabrics of geyserites around hot spring pools in Daggyai, Tibet, China. (12th May 2020) - Li, Rong; Wu, Geng; Jones, Brian; Shi, Taiheng
Abstract: The Daggyai geyserites serve as hosts for cesium deposits; however, their origin, whether by chemical deposition or biological formation, is a topic of debate. To decipher the origin of geyserites, the petrographic features of the geyserite samples were examined. The geyserites exhibited columnar laminated, planar laminated and spicular morphologies. Furthermore, they contained morphological and confocal microscopic evidence of the coccoid, bacilliform and filamentous microbes that formed them. Minor calcite and quartz crystals were found locally in the columnar laminated and spicular geyserites. Cyanobacteria tentatively assigned to the genus Calothrix dominated in the planar and columnar laminated geyserites, but were rare in the spicular geyserites. The results demonstrated that the microbes contributed to the Daggyai geyserite formation.